Growth, hardness and laser damage threshold studies on vertical Bridgman grown piperine (PPN) single crystal. (2nd January 2017) - Muthuraja, A.; Kalainathan, S.
Abstract : An organic piperine (PPN) single crystal was grown using vertical Bridgman technique. The diffraction planes have been indexed from powder X-ray diffraction analysis. Vickers microhardness studies were carried out on grown PPN crystal with various load ranging from 10 to 100 g. Reverse indentation size effect (RISE) is observed from the microhardness measurements. The meyer index value ( n ) was found to be greater than 1.6 which indicates the grown crystal belongs to soft-material category. The stiffness constant ( C 11 ) was computed using the Wooster's empirical relation. Laser damage threshold studies have been carried out using Q-switched Nd: YAG laser. All the results are discussed in detail.